Perbedaan Lama Rawat Inap Pada Pasien Sindrom Koroner Akut Dengan Stres Hiperglikemia Dan Tanpa Stres Hiperglikemia Non Diabetik Di Rsud Dr. Moewardi - Rezki, Yuniana Nur; , Dr. Iin Novita Nurhidayati Mahmuda., M.Sc, Sp.PD (2017)
Background: Acute Coronary Syndrome (ACS) in several recent studies related to hyperglycemia on admission to the higher mortality rates. Hyperglycemia in patients with ACS describes the acute response of hyperadrenergic state with an increasing risk of thrombosis. So it can worsen the condition of patients with ACS during hospitalization. Purpose: To determine differences between length of stay in ACS in patients with and without non-diabetic stress hyperglycemia. Methodology: In an observational study design and analytic approach cross sectional. Subject study were patients of ACS non diabetic RSUD Dr. Moewardi. Data obtained from medical records by using purposive sampling, with a total sample of 68 patients, 34 patients with hyperglycemia and 34 patients without hyperglycemia ACS. Data were analyzed using the Mann-Whitney test. Result: The result shows that there are differences in length of stay of ACS patients with and without the stress of non-diabetic hyperglycemia. With a median value for the group ACS with hyperglycemia is 6 days, while group ACS without hyperglycemia is 4 days. With the significant value of p = 0.002. Conclusion: There are differences in length of stay in ACS in patients with and without non-diabeti stress hyperglycemia in RSUD Dr. Moewardi.